2009
DOI: 10.1086/605722
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Oral Rinse with Chlorhexidine in Preventing Nosocomial Respiratory Tract Infections among Intensive Care Unit Patients

Abstract: Oral application of a 0.12% solution of chlorhexidine does not prevent respiratory tract infections among ICU patients, although it may retard their onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 34 publications
1
73
1
5
Order By: Relevance
“…According to the meta-analysis by Pineda et al, 44 which included four studies, the use of chlorhexidine as a local antiseptic of the oral cavity did not result in a lower incidence of VAP. 45 In contrast, our observations are in agreement with other reports showing that oral decontamination effectively decreased the incidence of VAP. [46][47][48] We found no differences in mortality, which is similar to the results reported by Segers et al 42 and Chan et al 36 This finding may be associated with the low expected mortality of our group of patients as predicted by Euro-SCORE, which was below 5%.…”
Section: Discussionsupporting
confidence: 93%
“…According to the meta-analysis by Pineda et al, 44 which included four studies, the use of chlorhexidine as a local antiseptic of the oral cavity did not result in a lower incidence of VAP. 45 In contrast, our observations are in agreement with other reports showing that oral decontamination effectively decreased the incidence of VAP. [46][47][48] We found no differences in mortality, which is similar to the results reported by Segers et al 42 and Chan et al 36 This finding may be associated with the low expected mortality of our group of patients as predicted by Euro-SCORE, which was below 5%.…”
Section: Discussionsupporting
confidence: 93%
“…Studies enrolled subjects expected to require orotracheal or nasotracheal intubation and mechanical ventilation. [8][9][10]12,14,15,[17][18][19]21,22,24,25 Among these, some studies required mechanical ventilation for at least 48 h. 10,12,22,24 Other studies only included subjects with medical conditions suggesting an ICU stay of Ն48 h, 15 3 d, 18 or 5 d 8,9 (Table 1). In 3 studies, research subjects were children.…”
Section: Subject Selection and Characteristicsmentioning
confidence: 99%
“…Among these antiseptics, chlorhexidine gluconate has attracted considerable attention, as evidenced by numerous randomized controlled clinical trials that have investigated the effect of oral chlorhexidine use in VAP prevention. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Results from the aforementioned randomized controlled trials and meta-analyses [26][27][28][29][30] that analyzed the effect of oral care with chlorhexidine on VAP prevention are conflicting. Discrepant findings may have resulted from differences in study populations, diagnostic criteria for VAP, chlorhexidine concentration, and frequency of use.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorhexidine at varying concentrations, however, has been evaluated in more than 11 trials. Impacts on VAP rates have been variable: three reported decreases [64][65][66] while the other eight did not [67][68][69][70][71][72][73][74]. One trial reported a decrease in antibiotic usage for patients treated with chlorhexidine [67].…”
Section: Oral Antiseptics and Antibioticsmentioning
confidence: 99%